100 ideas that changed graphic design - Heller, Steven, 1950-; Vienne, Véronique, ....- (London : King, 2015)
Eventually Harris stumbled upon an effective way to rein in that voice, something he always assumed to be either impossible or useless: meditation, a tool that research suggests can do everything from lower your blood pressure to essentially rewire your brain. 10% Happier takes readers on a ride from the outer reaches of neuroscience to the inner sanctum of network news to the bizarre fringes of America's spiritual scene, and leaves them with a takeaway that could actually change their lives.